2009
DOI: 10.1002/ps.1717
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic angiosperms, semagenesis and general strategies for plant–plant signaling in the rhizosphere

Abstract: Semagenesis enriches our understanding of the mechanisms available for small-molecule underground information exchange among plants. Critical differences in this process, as used by parasitic plants, are beginning to emerge and point towards new strategies for managing parasitic angiosperms in agricultural settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…26,39,40 We therefore utilized this straightforward assay to evalute the effects of compounds 1 – 17 on A. thaliana seedlings. The seedlings were examined following 12 days of exposure on media supplemented with a single, initial dose of compound at concentrations ranging from 10 –12 to 10 –4 M (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…26,39,40 We therefore utilized this straightforward assay to evalute the effects of compounds 1 – 17 on A. thaliana seedlings. The seedlings were examined following 12 days of exposure on media supplemented with a single, initial dose of compound at concentrations ranging from 10 –12 to 10 –4 M (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence implicates the semagenic quinones as not only regulating haustorial development in the parasitic plants [15], but more broadly in root meristem growth and development. The addition of semagenic quinones impacts development of both root architecture and notably root hair density in A. thaliana and N. tabaccum as well as the production of ROS [15] [48].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a good correlation between strigolactone exudation and field susceptibility for Striga attack, it was concluded that SXSg plays only a minor role, if any, in controlling germination of Striga seeds 58. Quinones, especially 2,6‐dimethoxyquinone (DMBQ), play an important role in the root elongation of germinated seeds and the haustorium formation 55, 56, 59…”
Section: Non‐strigolactones As Natural Germination Stimulantsmentioning
confidence: 99%